2015
DOI: 10.5455/2320-6012.ijrms20150340
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous tracheostomy by Griggs technique: a retrospective analysis

Abstract: Percutaneous tracheostomy (PCT) is emerging as a popular method to secure a definitive airway in ventilated patients in critical care units as an alternative to surgical tracheostomy. It offers several advantages such as ease of performance, small skin incision, less tissue trauma, lower infection rate, bedside conduct as well as optimum utilization of ICU personnel. 1,2 The scope of PCT is increasing with training and experience, with successful management of more and more scenarios which were earlier perceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In fact, there is a lack of efficient ventilation support in transporting to operation room that withdraws PEEP and has high portability of ventilator-induced lung injury development. 21 Lagoo et al 22 believed that the benefit of doing PDT in some contraindicated patients is sufficient, mainly by means of increasing training and experience in recent years, and rapid operation which minimizes the exposure time to any risk. In terms of patients requiring high PEEP, a RCT by Beiderlinden et al 23 revealed that the level of PEEP, procedure duration, and PDT technique are not accompanied by a significant deterioration in gas exchange.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there is a lack of efficient ventilation support in transporting to operation room that withdraws PEEP and has high portability of ventilator-induced lung injury development. 21 Lagoo et al 22 believed that the benefit of doing PDT in some contraindicated patients is sufficient, mainly by means of increasing training and experience in recent years, and rapid operation which minimizes the exposure time to any risk. In terms of patients requiring high PEEP, a RCT by Beiderlinden et al 23 revealed that the level of PEEP, procedure duration, and PDT technique are not accompanied by a significant deterioration in gas exchange.…”
Section: Discussionmentioning
confidence: 99%
“…Tracheostomy, either surgical or percutaneous, is a commonly performed procedure in intensive care units (ICU). This surgical intervention aims to provide a safe airway to those critically ill patients dependent on prolonged mechanical ventilatory support or those requiring an alternative airway for various reasons [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…PDT offers many benefits, including ease of application, smaller incision, less tissue trauma, lower rate of infection, use at bedside, and optimal utilization of ICU personnel [ 3 ]. Therapeutic use and indications of PDT may easily expand in most previously contraindicated conditions if training, experience, and successful management is provided [ 1 ]. PDT facilitates clearance of pulmonary secretions, reduces risk of subglottic stenosis secondary to endotracheal tube, decreases the need for sedative use in the ICU, and promotes early weaning from a mechanical ventilator.…”
Section: Introductionmentioning
confidence: 99%